The EU transit procedures and regional integration: the case of Ukraine - Kril, Roman; Кріль, Р. В.; Криль, Р. В. (Одеса : Видавничий дім «Гельветика», 2020)
The research evaluates the current EU legal framework for customs transit procedure with a view of promotion of regional integration through extension of transit procedures to EU neighbor countries. The article analyzes the formation of EU secondary legislation and its international agreements relating to introduction and application of transit procedure. Particularly, the relation of emerging of common transit procedure to the demands of Article X of GATT and early developments of TIR convention is reveled. The transition from bi-lateral to multilateral approach to extension of EU customs rules on transit is also emphasized. The typology of EU legal orders (including EU transit, Common transit, TIR transit, etc.) for application of transit procedure is reviewed with the focus at the high level of integration between such legal orders. The issue is considered as an example of Europeanization of customs law and administrative procedural law in general. Besides, the specific case of Ukrainian steps towards implementation of the Common transit procedure is analyzed. The comparative analyses of the relevant provisions of the Convention on Common Transit Procedure and the Law of Ukraine implementing such procedure shows the main gaps and possible issues that may become obstacles to successful joining the above mentioned Convention. У цьому дослідженні здійснено оцінку діючої законодавчої бази ЄС щодо митного транзиту з метою сприяння регіональній інтеграції шляхом розширення транзитних процедур на сусідні країни ЄС. У статті проаналізовано формування вторинного законодавства ЄС та його міжнародних угод, що стосуються запро- вадження та застосування транзитної процедури. Зокрема, виявлено взаємо- зв’язок виникнення загальної транзитної процедури з вимогами статті X ГАТТ 68 та ранніми розробками конвенції МДП. Також підкреслюється перехід від двостороннього до багатостороннього підходу до розширення митних правил ЄС щодо транзиту. Переглядається типологія правових норм ЄС (включаючи транзит ЄС, загальний транзит, транзит МДП тощо) для застосування транзитної процедури з акцентом на високому рівні інтеграції таких правових норм. Це питання розглядається як приклад європеїзації митного права та адміністративного процесуального права загалом. Крім того, проаналізовано конкретні кроки України щодо впровадження спільної транзитної процедури. Порівняльний аналіз відповідних положень Конвенції про загальну транзитну процедуру та Закону України, що імплементує таку процедуру, показує основні прогалини та можливі питання, які можуть стати перешкодою для успішного приєднання до вищезазначеної Конвенції.
Процедури транзиту в ЄС та регіональна інтеграція: приклад України
Kril R. The EU transit procedures and regional integration: the case of Ukraine/ R. Kril // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА “Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2020. - № 1. – C. 51 - 68.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; EU transit procedure; Common transit procedure; customs law; New Computerized Transit System; Association Agreement; Ukraine; транзитна процедура ЄС; загальна процедура транзиту; митне законодавство; нова комп’ютеризована система транзиту; Угода про асоціацію; транзитная процедура ЕС; общая процедура транзита; таможенное законодательство; новая компьютеризированная система транзита; Соглашение об ассоциации